History of Sepsis - Dr. Devendra Prasad K J (Story of Sepsis, Edition 1, 2025)
Sepsis, originating from the Greek term "\(ση Ψ\)l\(ζ\)" (decomposition), has experienced considerable transformation in its interpretation. Initial mentions by ancient scholars such as Homer and Hippocrates, who advocated for a balance of bodily humors, established foundational concepts regarding sepsis as a severe condition associated with tissue deterioration. The 20th century introduced a more precise definition through Schottmuller, in conjunction with the germ theory proposed by van Leeuwenhoek, Pasteur, and Koch, which clarified the microbial origins of infections and catalyzed significant progress in sanitation and the development of antibiotics. The implementation of hand hygiene protocols in obstetrics by Semmelweis represented a significant advancement in the domain of infection control, notwithstanding initial doubts, and laid the groundwork for practices that are indispensable in contemporary healthcare. The utilization of germ theory by Joseph Lister in surgical contexts further transformed infection prevention strategies, thereby improving patient outcomes through the adoption of antiseptic techniques. Together, the contributions of these individuals have greatly enhanced the comprehension of sepsis and the dynamics of infectious diseases, underscoring the essential importance of managing toxins and controlling infections within the healthcare system.